The Biochemical Characterization Of Neuronal K+ Channel N-Glycans And Their Role In Regulating K+ Channel Function - Cartwright, Tara A. (East Carolina University, 2009)
The Kv3 and Kv1 subfamilies of voltage–gated K+ channels are critical components which contribute to action potential repolarization throughout the central nervous system. Here, it was shown that both absolutely conserved N–glycosylation sites of the Kv3.1, Kv3.3 and Kv3.4 proteins were occupied in the central nervous system of the adult rat by complex oligosaccharides. Additionally, it was demonstrated that the expression patterns of the Kv3 glycoproteins were different from one another throughout the central nervous system. Electrophoretic migration patterns of the Kv3 glycoproteins from different membranes of the central nervous system digested with glycosidases were utilized to identify the attachment of unique sialylated N–glycan structures. An examination of these sialylated N–glycan structures revealed that the Kv3 glycoproteins, along with the Kv1.1, Kv1.2, and Kv1.4 glycoproteins, were terminated with atypical disialyl units. Moreover, at least one of the carbohydrate chains of the Kv3.1, Kv3.3 and Kv3.4 glycoproteins, like Kv3.1 heterologously expressed in B35 cells, was capped with an oligo/polysialic acid unit. Notably, this is the first time that di/oligo/polysialyl units have been shown to be associated with K+ channels. Sialyl residues linked to internal carbohydrate residues were shown to be components of the N–glycans of the Kv1 glycoproteins, as well as the Kv3 glycoproteins and N–CAM. To date, this unusual glycosidic bond for sialyl residues has not been identified on N–glycans. Whole cell current measurements of glycosylated (wild type), unglycosylated mutant (N220Q/N229Q) and partially glycosylated mutant (N220Q and N229Q) Kv3.1 channels heterologously expressed in B35 cells revealed that the glycosylated Kv3.1 protein could favor a subpopulation of channels with fast activation and inactivation rates for inactivating currents. However, this subpopulation was undetectable for the inactivating currents of the unglycosylated and partially glycosylated Kv3.1 channels. Additionally, the noninactivating current type of the glycosylated and partially glycosylated Kv3.1 channels revealed a subpopulation of Kv3.1 channels with fast activation and inactivation rates, as well as with fast activation and slow inactivation. We conclude that the presence of atypical sialylated N–glycans of Kv3 glycoproteins, and perhaps Kv1 glycoproteins, in mammalian brain is critical in modulating the expression of K+ currents at the surface of neurons.
Keywords: Biology, Neuroscience; Channel function; N-glycosylation; Rat brain; Sialic acid; Voltage-gated K+ channel; Neuroscience; Glycoproteins; Potassium Channels